Language learning needs analysis for the Reform of the omani grade 11 EFL program / Said Hamed Rashed Al- Saadi - Said Hamed Rashed, Al- Saadi (2013)

(untitled)
To develop a national framework of needs analysis, the present study investigated the English language learning needs of the Omani Grade 11 EFL students. Using a multidimensional model of needs analysis, it addressed the language use context, the English language instruction context, the learners’ motivation and goal context, and Means Analysis context. The research questions covered each of the needs dimensions and examined the competing discourse found between the different stakeholders. In order to put needs analysis on a sound theoretical and empirical base, the present study examined the needs of new explored population by addressing the language learning needs of the pre-university/school level students in the Arab world. Multiple sources, such as 982 students, 64 teachers, 4 supervisors, 3 heads of department and 4 English language textbooks were approached for data collection. In addition, a variety of data was gathered and compared using multiple methods such as questionnaires, interviews, and textbook analysis. Textbook analysis revealed that reading skill and listening skill were the language macro skills used most frequently whereas little attention was paid to speaking and writing skill. Most of the teachers, supervisors and heads of department perceive speaking as the most important skill to be taught for the Grade 11 students and listening as the least important skill. The subject of needs analysis (NA) had not yet received sufficient attention from researchers and language teaching professionals in the Omani educational system. It was found that the Grade 11 EL curriculum did not meet the perceived needs of Omani students according to the expectations of students, teachers, supervisors and heads of department. The majority of respondents considered that the purpose of the Grade 11 EL program was to prepare the students well to pass the General Diploma examination. The majority of the teachers, supervisors and heads of department were not satisfied with the Grade 11 EL program. Examining the comporting discourse among different stakeholders revealed that there was significant difference found between teachers and students in their attitudes toward the current English Language program in Grade 11, in their perception of writing and speaking difficulties. No statistically significant difference was found between urban and rural students in their perception of the EL learning needs of Omani students in Grade 11. Finally no significant difference was found between female and male students in their attitudes toward the current English language program and in their perception of writing and speaking difficulties.. The implementation needs of the study findings were analyzed and were provided in reference to the theoretical and the methodological implications, the underpinning principles and content implications, the teaching material and methodology implications, and the implications for teacher training and assessment.